GENDER DIVERSITY OF EXECUTIVE, INTERNAL CONTROL, INSTITUTIONAL OWNERSHIP, FIRM SIZE AND TAX AVOIDANCE: AN INTERACTIVE EFFECTS BUSINESS STRATEGY - Mardjono, Enny Susilowati (Universitas Jember, 2024)
ABSTRACTBusiness strategy is crucial for companies to improve performance and map business opportunities and challenges to achieve maximum profits. This research aims to analyze the influence of gender diversity of executives, internal control, institutional ownership, and firm size on tax avoidance. An empirical study on manufacturing companies listed on the IDX for 2019 – 2023. This research contributes by considering the business strategy carried out by the company, which allows it to increase company profits. The number of data samples in this study was 41 manufacturing companies, and the total number of observations was 205. This research shows that gender diversity and institutional ownership do not affect tax avoidance. However, the gender diversity of executives and internal control influences tax avoidance. The results provide further insight into how companies use business strategies by considering executive gender diversity, internal control institutional ownership, and firm size to increase the effectiveness of tax avoidance.Keywords: Firm Size; Gender Diversity; Institutional Ownership; Internal Control; Tax Avoidance ABSTRAKStrategi bisnis sangat penting bagi perusahaan untuk meningkatkan kinerja dan memetakan peluang dan tantangan bisnis untuk mencapai keuntungan maksimal. Penelitian ini bertujuan untuk menganalisis pengaruh gender diversity of executives, internal control, dan institutional ownership, firm size pada tax avoidance. Studi empiris pada perusahaan pertambangan yang terdaftar di BEI periode 2019-2023. Penelitian ini memberikan kontribusi dengan mempertimbangkan strategi bisnis yang dilakukan perusahaan yang memungkinkan dapat meningkatkan keuntungan perusahaan. Jumlah sampel data dalam penelitian ini sebanyak 41 perusahaan manufaktur dan jumlah observasi sebanyak 205. Hasil penelitian menunjukkan bahwa gender diversity, dan institutional ownership tidak berpengaruh terhadap tax avoidance. Namun, internal control dan firm size mempengaruhi tax avoidance. Hasilnya memberikan wawasan lebih lanjut tentang bagaimana perusahaan menggunakan strategi bisnis dengan mempertimbangkan gender eksekutif, pengendalian internal, kepemilikan institusional dan ukuran perusahaan untuk meningkatkan efektivitas penghindaran pajak.Kata Kunci: Gender Diversity; Kepemilikan Institusional; Pengendalian Internal; Penghindaran Pajak; Ukuran Perusahaan